AI-Driven Innovations in Automotive Safety: High-level Analysis - Aravind, Ravi; Vinalbhai Shah, Chirag (International Journal of Scientific Research and Management (IJSRM), 2022)
Safety in the transportation sector has been of particular concern to policymakers, industry participants, and the scholarly community. The continued steady progress in scientific knowledge and technological progress has resulted in a decrease in fatal accidents. The ever-decreasing cost of computing power has created the preconditions for a new round of innovative solutions that use AI-driven technologies to enhance automotive safety. In this study, we provide a scientific-technical survey of AI-driven innovations in vehicle safety, underscore potential barriers to large-scale implementation, and provide policy recommendations. The results are intended to assist policymakers, researchers, and practitioners in a wide range of domains in understanding the potential effects of AI-driven technologies on vehicle safety.